SnCl2·2H2O and Ni(OAc)2·4H2O: Efficient Heterogeneous Inorganic Catalysts for the Chemoselective Synthesis of Geminal Diacetates (Acylal) Under Solvent-Free Conditions - Khazaei, Ardeshir; Amini Manesh, Abbas; Ali Alavi-Nik, Heidar; Toodeh Roosta, Zahra (Asian Journal of Chemistry, 2010)
SnCl2·2H2O and Ni(OAc)2·4H2O were found to be efficient catalysts for preparation of 1,1- diacetates under solvent-free conditions at room temperature. Easy work-up and low cost are important features from the environmental and economical points of view, are distinct aspects of this research. Very good to exellent yields, short reaction times, non-toxicity and stability of the catalysts are noteworthy advantages of this method.